2022
DOI: 10.3390/plants11182337
|View full text |Cite
|
Sign up to set email alerts
|

GmSWEET29 and Paralog GmSWEET34 Are Differentially Expressed between Soybeans Grown in Eastern and Western Canada

Abstract: Over the past two decades soybeans grown in western Canada have persistently had lower seed protein than those grown in eastern Canada. To understand the discrepancy in seed protein content between eastern- and western-grown soybeans, RNA-seq and differential expression analysis have been investigated. Ten soybean genotypes, ranging from low to high in seed protein content, were grown in four locations across eastern (Ottawa) and western (Morden, Brandon, and Saskatoon) Canada. Differential expression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…Lu et al 2022). We also found seed-specific expression of GmSWEET23 (Glyma.08G077200), GmSWEET4 (Glyma.04G198400), and GmSWEET39/GmSWEET10a (Glyma.15G049200), which were also associated with seed oil and protein content (Hooker et al 2022;C. Liu et al 2023;H.…”
Section: Identification Of Oil Candidate Genes With High Expression I...supporting
confidence: 58%
“…Lu et al 2022). We also found seed-specific expression of GmSWEET23 (Glyma.08G077200), GmSWEET4 (Glyma.04G198400), and GmSWEET39/GmSWEET10a (Glyma.15G049200), which were also associated with seed oil and protein content (Hooker et al 2022;C. Liu et al 2023;H.…”
Section: Identification Of Oil Candidate Genes With High Expression I...supporting
confidence: 58%
“…20g082700 (sugar efflux transporter SWEET52) are presumed to be involved in protein, carbohydrate, and lipid metabolism during soybean seed development. These studies have shown that these genes would affect protein content after seed maturity [38,42,43,48,49]. However, there are few specifically studied and identified genes within this interval.…”
Section: Discussionmentioning
confidence: 99%
“…The genes Glyma.15g108000, Glyma.15g108900, Gylma.18g193600, and Glyma.20g082700 (related to starch and carbohydrates synthesis during seed development), Glyma.18g195700, Glyma.18g195900, Glyma.18g196000 (associated with fatty acid biosynthesis), and Glyma.20g081500 (related to lipid catabolic processes during seed development) are likely to regulate protein accumulation. These candidate genes may regulate protein accumulation by influencing the sugar delivery from the seed coat integument to the embryo [38,40,43]. Several studies on soybean RIL populations have reported that seed protein, sucrose, and oil content show negative correlations [4,19,25,27,28,32,51].…”
Section: Discussionmentioning
confidence: 99%
“…While growing season precipitation was higher in Eastern Canada, the difference between the Eastern Prairie (80% of Eastern Canada) and Prairie (47% of Eastern Canada) sites (Table 1) did not correspond with the lack of yield difference (Table 4). In molecular biology approach to this experiment, gene expression analysis found that there were differences in expression of sugar transporters (GmSWEET genes) in Eastern versus Western Canada (Hooker et al 2022) and differential sugar transporter gene expression could play a role in photosynthate movement or allocation leading to regional differences in seed yield and composition. The yield difference between Eastern Canada and Eastern Prairie in our study was similar to the difference reported between southern Manitoba and Ottawa (Ort et al 2022).…”
Section: Seed Protein Contentmentioning
confidence: 99%